Severe Hemorrhagic Shock Leads to a Delayed Fracture Healing and Decreased Bone Callus Strength in a Mouse Model. Issue 11 (November 2017) - Bundkirchen, Katrin; Macke, Christian; Reifenrath, Janin; Schäck, Luisa Marilena; Noack, Sandra; Relja, Borna; Naber, Philipp; Welke, Bastian; Fehr, Michael; Krettek, Christian; Neunaber, Claudia
Abstract: Background: Multiple trauma is frequently associated with hemorrhagic shock and fractures of the extremities. Clinically, the rate of impaired fracture healing (delayed healing and nonunion) seems to be increased in patients with multiple injuries compared with patients with isolated fractures. As the underlying pathogenesis remains poorly understood, we aimed to analyze the biomechanical properties during fracture healing in a murine model. Questions: The aim of this study was to determine whether fracture healing after severe hemorrhagic shock results in (1) delayed bridging as determined by macroscopic and radiographic assessment, (2) altered conditions of callus components as determined by μCT, and (3) decreased maximum bending moment measured by a three‐point‐bending test compared with ordinary fracture healing. Methods: Male C57BL/6NCrl mice were randomly assigned to five groups and four different times (five to 10 mice per group and time). Only the right femur from each mouse was used for analysis: the trauma hemorrhage (TH) group received a pressure‐controlled hemorrhagic shock via catheter; the osteotomy (Fx) group underwent osteotomy and implantation of an external fixator on the right femur; the combined trauma (THFx) group received hemorrhagic shock and an external fixator with osteotomy; the sham group underwent implantation of a catheter and external fixator but had no blood loss or osteotomy, and the control group underwent no interventions. After 2, 3, 4, or 6 weeks, five to 10 animals of each group were sacrificed. Bones were analyzed macroscopically and via radiographs, μCT, and three‐point‐bending test. Statistical significance was set at a probability less than 0.05. Comparisons were performed using the Mann‐Whitney U or the Kruskal‐Wallis test. Results: In the Fx group, the osteotomy gap was stable and bridged after 2 weeks in contrast to some bones in the THFx group where stable bridging did not occur. No difference was observed between the groups. μCT analysis showed reduced density of bone including callus (THFx: 1.17 g/cm 3 ; interquartile range [IQR], 0.04 g/cm 3 ; Fx: 1.22 g/cm 3 ; IQR, 0.04 g/cm 3 ; p = 0.002; difference of medians [DM], −0.048; 95% CI, −0.073 to −0.029) and increased share of callus per volume of bone mass (%) after 2 weeks in the THFx group compared with the Fx group (THFx: 44.16%; IQR, 8.66%; Fx: 36.73%; IQR, 4.39%; p = 0.015; DM, 7.634; 95% CI, 2.018‐10.577). The three‐point‐bending test established a decreased maximum bending moment in the THFx group compared with the Fx group 2 weeks after surgery (THFx: 7.10 Nmm; IQR, 11.25 Nmm; Fx: 11.25 Nmm; IQR, 5.70 Nmm; p = 0.026; DM, −5.043; 95% CI, −10.867 to −0.74). No differences were observed between the THFx and Fx groups after more than 2 weeks. Conclusion: In this in vivo mouse fracture model, we conclude that hemorrhagic shock retards fracture healing during the early phase of the facture healing process. Clinical Relevance: A severe hemorrhagic shock in patients could result in initial delayed fracture healing and needs special attention. We plan to conduct a prospective, observational clinical research study to analyze if delayed fracture healing occurs in patients after severe blood loss.